1982
DOI: 10.1111/j.1151-2916.1982.tb10512.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of Uranium in Aluminophosphate Glasses

Abstract: The U(VI)-U(V)-U(IV) redox equilibria were monitored in two sodium aluminophosphate base compositions at a variety of melt temperatures, imposed oxygen fugacities, and uranium contents. The higher redox states of uranium were quite soluble in the phosphate glasses, whereas U(1V) would readily precipitate from the melts as UO,. Comparisons of the uranium redox equilibria established in phosphate melts vs those in silicate melts indicated that the coordination sites of the individual uranium species are generall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Uranium oxidation state in glasses also depends on melting temperature -higher melting temperature reduces fraction of U(VI) in favor of U(V) and U(IV) [16], type of uranium compound introduced in the batch, for example, incorporation of UO 2 in a melt with sodium metaphosphate composition results in partial oxidizing of uranium [18], and occurrence of multivalent elements participating in redox reactions with U ions in glass -incorporation of iron oxides in U-bearing borosilicate glasses reduces the U(VI)/U(IV) ratio [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uranium oxidation state in glasses also depends on melting temperature -higher melting temperature reduces fraction of U(VI) in favor of U(V) and U(IV) [16], type of uranium compound introduced in the batch, for example, incorporation of UO 2 in a melt with sodium metaphosphate composition results in partial oxidizing of uranium [18], and occurrence of multivalent elements participating in redox reactions with U ions in glass -incorporation of iron oxides in U-bearing borosilicate glasses reduces the U(VI)/U(IV) ratio [15].…”
Section: Introductionmentioning
confidence: 99%
“…Uranium may be present in nuclear wastes [7,8] and thus incorporated into waste glass at vitrification, introduced in glass to produce special optical glasses [9] or occurs in natural glasses [10]. In both silicate [10][11][12][13][14][15] and phosphate glasses [16][17][18][19][20] uranium under standard melting (slightly oxidizing) conditions is present as major U(VI), secondary in abundance U(V), and minor U(IV). We know the only work [21] where U in iron phosphate glass was found to be predominantly U(IV).…”
Section: Introductionmentioning
confidence: 99%
“…ior of uranium oxides in aluminophosphate melts primarily revealed good solubility of UO 3 , although the solubility has not been determined accurately, which is mainly associated with the diversity of uranium valence states [12,13]. The solubility of UO 2 is considerably lower.…”
Section: Resultsmentioning
confidence: 99%
“…
Investigation of the oxidation state and structural positions of uranium in glasses as functions of their composition is of interest for analyzing the behavior of multivalent elements in high temperature melts and for designing glasses for immobilization of some types of radioactive waste.Whereas the state of uranium in silicate and boro silicate melts and glasses has been studied in sufficient detail (see review [1] and original articles [2][3][4][5]), the state of uranium in phosphate glasses was explored in very few articles [6][7][8]. The latter showed that sodium aluminophosphate glasses, as well as sodium (boro) silicate ones, under oxidizing glass melting conditions are dominated by U(VI) in the form of uranyl ions UO , with the U(VI) concentration decreasing with increasing glass melting temperature [6,7], whereas sodium free and low sodium iron phosphate glasses are dominated by U(IV) [8].
…”
mentioning
confidence: 99%
“…The latter showed that sodium aluminophosphate glasses, as well as sodium (boro) silicate ones, under oxidizing glass melting conditions are dominated by U(VI) in the form of uranyl ions UO , with the U(VI) concentration decreasing with increasing glass melting temperature [6,7], whereas sodium free and low sodium iron phosphate glasses are dominated by U(IV) [8]. In this work, for the first time, we studied the oxidation state and coordination environment of uranium in high sodium iron alumi nophosphate glasses.…”
mentioning
confidence: 99%